A new species of Syzygium (Myrtaceae) from Kerala, India - Shareef, S.m.; Kumar, Santhosh; Roy, P.e. (Phytotaxa, 2013)
A new species of Syzygium, S. chemunjianum is described and illustrated from the Agasthyamala Biosphere Reserve, southern Western Ghats, Kerala, India. It is similar to S. tamilnadensis but differs from it in habit, colour and nature of blaze, shape of leaves, number of intramarginal nerves, position of inflorescence, the colour, size and shape of fruits and size of seeds.